2012
DOI: 10.1039/c1jm13952e
|View full text |Cite
|
Sign up to set email alerts
|

Single nanoparticle of organic p-type and n-type hybrid materials: nanoscale phase separation and photovoltaic effect

Abstract: We fabricated hybrid nanoparticles (NPs) of p-type poly(3-hexylthiophene) (P3HT) and n-type fullerene derivative {[6,6]-phenyl C 61 -butyric acid methyl ester (PCBM)} materials through a miniemulsion method. The nanoscale photoluminescence (PL) characteristics of the non-annealed and annealed hybrid single NPs with different concentrations of P3HT and PCBM were investigated using a laser confocal microscope (LCM) with high spatial resolution. The luminescence characteristics corresponding to the P3HT and PCBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…At this time, a local electric field generated around AuNPs, which in turn enhanced the electron-hole recombination of CdS QDs. [32,33] While energy acceptors of the AuNPs were removed, the sensitization of CdS QDs on TiO 2 recovered and meanwhile the photocurrent output obviously picked up. Indirectly, the EET could be applied to regulate the photocurrent signal of the PEC system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, a local electric field generated around AuNPs, which in turn enhanced the electron-hole recombination of CdS QDs. [32,33] While energy acceptors of the AuNPs were removed, the sensitization of CdS QDs on TiO 2 recovered and meanwhile the photocurrent output obviously picked up. Indirectly, the EET could be applied to regulate the photocurrent signal of the PEC system.…”
Section: Resultsmentioning
confidence: 99%
“…[30,31] It could effectively reduce photocurrent output through increasing the electron-hole recombination of the photoactive energy donors. [32,33] Generally, the absorption and emission spectral overlap coupled with the proper distance between energy donor and acceptor (10 AE 2 nm) are the two necessary conditions for the occurrence of EET. In various photoactive materials, semiconductor QDs are considered as the ideal energy donors for their broad excitation, photochemical stability, regulated emission spectra, and easy modification.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence intensity of QDs is enhanced by the PRET phenomenon that occurs via interaction between QDs and plasmonic NPs or CNMs. [77] In this case, the collective effect in a hybrid structure consisting of plasmonic materials and fluorescent nanoparticles enhances the fluorescence. [78] To detect viruses, DNA, RNA, and biomolecules, PRET-based FIs have been developed by using several plasmonic nanomaterials, including MeNPs, core/shell NPs, MeNP-CNMs, inorganic QDs, carbon dots, and GRP-QDs.…”
Section: Fluorescent Qds For Biosensing Systemsmentioning
confidence: 99%
“…The first NPOPV devices based on the more common P3HT:PCBM system were reported by Lee et al, who synthesised P3HT:PCBM NPs using the miniemulsion method and then demonstrated their PV effect using conducting atomic force microscopy (AFM) under illumination [35]. At almost the same time, Larsen-Olsen et al reported fully-printed reel-to-reel (R2R) devices using an inverted geometry also based on P3HT:PCBM NPs that exhibited a best PCE of only 0.3% [22].…”
Section: The P3ht:pcbm Npopv Materials Systemmentioning
confidence: 99%